Strengthening the Nation's Ideology Values in the Framework of Strengthening National Resilience in the Global Level - Widjojo, Agus (Law Research Review Quarterly, 2016)
The reform process currently underway is basically a process of reinventing and rebuilding and consolidating the Indonesian nation towards a modern democratic society and at the same time a corrective awareness to reorganize its life so that it becomes better for the achievement of its national goals and ideals. However, at the empirical level, it is indicated that the reforms have not yet proceeded as originally expected, namely as a process of systematic and measured change. This can be seen in the application of the rights of individual and group freedoms that even give rise to vertical and horizontal conflicts. On the other hand, the demands for regional expansion which are considered to be an expression of local freedom, in practice have grown wider and more difficult to control. The emergence of sectoral ego, regional ego, tribal ego, religious group ego, all of which often neglect harmony and harmony in the life of the nation and state.